2007
DOI: 10.1083/jcb.200604167
|View full text |Cite
|
Sign up to set email alerts
|

Organization of β-adrenoceptor signaling compartments by sympathetic innervation of cardiac myocytes

Abstract: The sympathetic nervous system regulates cardiac function through the activation of adrenergic receptors (ARs). β1 and β2ARs are the primary sympathetic receptors in the heart and play different roles in regulating cardiac contractile function and remodeling in response to injury. In this study, we examine the targeting and trafficking of β1 and β2ARs at cardiac sympathetic synapses in vitro. Sympathetic neurons form functional synapses with neonatal cardiac myocytes in culture. The myocyte membrane develops i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 55 publications
8
107
0
Order By: Relevance
“…The reason for the clustering pattern of protein expression is unknown but is likely to be related to its role in the regulation of heart function. It was recently shown that the ␤ 1 -adrenergic receptor is enriched at sites of sympathetic nerve synapses in cardiomyocytes (33). Interestingly, we also observed enriched GPR22 protein expression in the highly innervated cells of the sinoatrial node and atrioventricular node in rat hearts (data not shown).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The reason for the clustering pattern of protein expression is unknown but is likely to be related to its role in the regulation of heart function. It was recently shown that the ␤ 1 -adrenergic receptor is enriched at sites of sympathetic nerve synapses in cardiomyocytes (33). Interestingly, we also observed enriched GPR22 protein expression in the highly innervated cells of the sinoatrial node and atrioventricular node in rat hearts (data not shown).…”
Section: Discussionsupporting
confidence: 56%
“…In situ hybidization probes were generated from the TOPO II-GPR22 (mouse) plasmid using the RiboProbe In Vitro Transcription Kit (Promega) following the manufacturer's instructions. Sense and antisense 33 …”
Section: Methodsmentioning
confidence: 99%
“…In this model, both endogenous and exogenous SAP97 localizes exclusively at newly formed myocyte-myocyte contacts containing cadherins and connexin channels (1). Co-culture of cardiac myocytes and sympathetic neuronal cells has revealed another distinct localization of SAP97 at the contacts between nerve endings and myocytes, where the anchoring protein appears to be part of the ␤-adrenergic signaling complex (393). Taken together, these studies clearly indicate that SAP97 is not randomly distributed but is part of protein complexes involved in the formation of specialized membrane domains in cardiomyocytes.…”
Section: Figurementioning
confidence: 50%
“…Despite their sequence similarities, ␤ 1 AR does not behave like ␤ 2 AR following ligand binding. ␤ 1 AR internalizes at a higher rate in cardiomyocytes and does not relocalize away from contact sites with sympathetic ganglion neurons or out of caveolar fractions following ligand binding (36,37). Therefore, regulation of S-palmitoylation at the distal site by a specific subset of palmitoyltransferases could contribute to discrimination between these receptors.…”
Section: Discussion ␤ 1 Ar Is S-palmitoylated At Two Sites In Its Cytmentioning
confidence: 99%